Statistical aspects of acoustic returns from a wind-driven water surface covered with organic films - POGORZELSKI, S.J. (Archives of Acoustics, 1995)
The statistical properties of ultrasonic (10 MHz) signals scattered at a wind-driven water surface covered with different petroleum derivative films of well-defined and oceanographically relevant elastic surface properties were examined under laboratory and open-sea conditions. Evolution of the shape, skewness and kurtosis parameters of the signal distribution as a function of wind speed reflects a principal role played by the film elasticity. The elastic properties of composite sea surfaces likely to be present in nature and consisting of oil spills filled with a surface active material, floating solid particles, bubbles or drops of a third fluid with their important implications in remote sensing techniques are also discussed. A two-spatial scale irregularities distribution of the sea surface (capillary ripples present on tilted faces of long gravity waves) expresses itself in the corresponding signatures of at-sea experiment data.